2013
DOI: 10.1088/0957-4484/24/50/505706
|View full text |Cite
|
Sign up to set email alerts
|

Largely enhanced thermal and mechanical properties of polymer nanocomposites via incorporating C60@graphene nanocarbon hybrid

Abstract: Although considerable progress has been achieved to create advanced polymer nanocomposites using nanocarbons including fullerene (C60) and graphene, it remains a major challenge to effectively disperse them in a polymer matrix and to fully exert their extraordinary properties. Here we report a novel approach to fabricate the C60@graphene nanocarbon hybrid (C60: ~47.9 wt%, graphene: ~35.1%) via three-step reactions. The presence of C60 on a graphene sheet surface can effectively prevent the aggregation of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 33 publications
0
31
0
Order By: Relevance
“…Under common processing conditions, isotactic PP often shows an α crystalline form. Figure 3C shows that, in the XRD test, when 2θ was 14.1°, 16.8°, 18.5°, 21.3°, and 21.8°, the corresponding Bragg diffraction characteristic peaks of PP were accompanied by crystal plane diffraction of (110), (040), (130), (111), and (131) [1,[12][13][14]. The results illustrated that, for PP90/TPU10 and MPP/TPU, the diffraction peak remained the same, indicating that adding TPU did not create a new crystalline structure [15,16].…”
Section: Melting and Crystalline Behaviorsmentioning
confidence: 99%
“…Under common processing conditions, isotactic PP often shows an α crystalline form. Figure 3C shows that, in the XRD test, when 2θ was 14.1°, 16.8°, 18.5°, 21.3°, and 21.8°, the corresponding Bragg diffraction characteristic peaks of PP were accompanied by crystal plane diffraction of (110), (040), (130), (111), and (131) [1,[12][13][14]. The results illustrated that, for PP90/TPU10 and MPP/TPU, the diffraction peak remained the same, indicating that adding TPU did not create a new crystalline structure [15,16].…”
Section: Melting and Crystalline Behaviorsmentioning
confidence: 99%
“…Carbon-based nanomaterials such as carbon nanotube [134,135], nanodiamond [136] and C 60 [137] are generally considered to be eco-friendly materials with remarkable thermal characteristics, mechanical properties and flame retardancy. The use of carbon family materials to enhance the mechanical properties of polymer has been studied for a long time, but few studies are concerned about the effectiveness of carbon materials as a barrier in promoting the thermal stability of polymer and in inhibiting fire of flame retardants [104,138,139].…”
Section: Inorganic-nanomaterials Graphene-based Composite Flame Retarmentioning
confidence: 99%
“…In fact, for C 60 , not only act as the fortifiers for graphene and barriers but also have a free radical trapping effect in polymeric matrices. Song et al [137] incorporated C 60 into graphene via three-step reactions, and they found that the as-prepared C 60 @graphene exhibits uniform dispersion in PP matrices while the C 60 on the surface of GNs can prevent their aggregation. As a result, the interaction of nanofiller and polymer matrices is effectively improved and the mechanical properties of the PP-based composite are enhanced, thanks to the free radical-trapping effect of C 60 and the thermal barrier effect of graphene layers.…”
Section: Inorganic-nanomaterials Graphene-based Composite Flame Retarmentioning
confidence: 99%
“…Electronic polarization occurs during very short intervals of time, ionic polarization in the range of a few seconds, whereas the dipole polarization takes relatively longer durations [15]. Polymer nanocomposites are known to possess good barrier, mechanical properties [16], reduced flammability [17], increased heat distortion temperature [18] and reduced solvent uptake [19].…”
Section: Introductionmentioning
confidence: 99%
“…CuO, as a nanopowder has also been used as a catalyst in adsorption studies for wastewater treatment and for antimicrobial applications [13]. In addition to this, CuO nanoparticles find applications in nanofluids [14]; CuO and Cu 2 O nanospheres are used in sensitive gas sensors [15] and in supercapacitors [16] as well.…”
Section: Introductionmentioning
confidence: 99%